2021
DOI: 10.1051/e3sconf/202131407001
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring study of trace metals (Al, As, Li) in mussels from Al Hoceima coastline of Moroccan Mediterranean Sea

Abstract: Mytilus galloprovincialis are commonly used as heavy metal biomonitors across the world. In the present work, the contents of three elements (Al, As, Li) were analyzed in Mytilus galloprovincialis using Inductively Coupled Plasma – Optical Emission Spectrometry (ICP-OES 720-ES). Samples of soft tissues are collected monthly in 2020, from three sites of the mussel farming facilities installed in the Al Hoceima Sea. The decreasing order of the mean element contents in mussel tissues was Al > As > Li. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The presence of REEs in aquatic environments, such as estuaries, may have an impact towards their biological resources. Among them bivalves are socio-economically important (WHO, 2010) and have been widely recognized as good bioindicators in both monitoring and ecotoxicological studies (Azizi et al, 2018;Belivermiş et al,2016;Rouane-Hacene et al, 2015). Although the effects of La are still poorly understood, in the Mediterranean mussel Mytilus galloprovincialis this element has seen to bioaccumulate and trigger changes in their metabolism, energy reserves content and antioxidant and biotransformation processes (Pinto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of REEs in aquatic environments, such as estuaries, may have an impact towards their biological resources. Among them bivalves are socio-economically important (WHO, 2010) and have been widely recognized as good bioindicators in both monitoring and ecotoxicological studies (Azizi et al, 2018;Belivermiş et al,2016;Rouane-Hacene et al, 2015). Although the effects of La are still poorly understood, in the Mediterranean mussel Mytilus galloprovincialis this element has seen to bioaccumulate and trigger changes in their metabolism, energy reserves content and antioxidant and biotransformation processes (Pinto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among pollutants, published information has already revealed that bioaccumulation of metal(oid)s can lead to toxic effects in bivalves, namely in mussels, including the alteration of their metabolism and redox status (Binelli et al, 2011;Errahmani et al, 2014;Freitas et al, 2018, Manduzio et al, 2005Savorelli et al, 2017). In particular, studies conducted with metal(loid)s on the top list of the most hazardous materials, such as Mercury (Hg), Arsenic (As), Copper (Cu) and Cadmium (Cd), already showed the capacity of these elements to activate mussel's antioxidant defence mechanisms and decrease their metabolic capacity (Azizi et al, 2018;Coppola et al, 2018a,b;Mubiana and Blust, 2007;Nardi et al, 2017;Raftopoulou et al, 2011). Among the most widely distributed hazardous materials throughout the environment it is identified Lead (Pb) (ATSDR, 2017) due to its use in a vast diversity of anthropogenic activities (e.g.…”
Section: Introductionmentioning
confidence: 99%